A Study to find out the Teaching Methods in Secondary Schools of Zarghoon Town, Quetta - Azeem, Shazia; Kiazai, Dr. Abdul Nasir (Journal of Quranic and Social Studies, 2022)
Teaching techniques are viewed as a perplexing space. They are subject to epistemological convictions, impacted by the discipline, and include a 'blend of systems and definitions whereupon the scholarly community can't conform. Teaching methods plays a vital role in teaching and learning process. The objectives of this thesis was to analyze the current teaching methods in secondary schools of Zaghoon Town Quetta and also teachers perceptions of best and effective teaching methodologies in secondary schools and to suggest best teaching methods for future teaching process. The results found that there is a traditional teaching method followed by most of the teachers. No constructive method of teaching was found. The students learning outcomes were not achieved through traditional teaching method. It was concluded that low interest of teachers toward new teaching methods, lack of teaching material, unskilled or less trained teachers, and ineffective teaching methods can result in an unsatisfied and boring classroom. Besides, it was observed that there is no personal interest of teachers involved to encourage their students to acquire new ideas, to use internet facilities and other teaching aids. It was recommended that government should arrange in service training facilities to all secondary school teachers and trainings should introduce new and effective teaching methods through which the teachers fulfill their teaching objectives.